2003
DOI: 10.1159/000072730
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Acupuncture for the Treatment of Primary Dysmenorrhea

Abstract: Objective: The aim of this study was to evaluate the effect of acupuncture (AP) in the treatment of primary dysmenorrhea (PD). Methods: A clinical prospective, placebo-controlled trial included 57 women with PD. Of these, 30 were treated with manual AP points: Du 20 (Baihui), bilateral Li 4 (Hegu), Ren 3 (Zhongji), Ren 4 (Guanyuan), Ren 6 (Qihai), bilateral Gb 34 (Yanglingquan), bilateral Ub 23 (Shenshu), bilateral Lp 6 (Sanyinjao) and auriculoacupuncture points (Shenmen); 27 women were treated with placebo AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…A recent research showed that acupuncture point injection with vitamin K can alleviate acute menstrual pain, and the relief extended through the nontreatment follow-up cycles in an uncontrolled pilot study, which was conducted in two countries (Wang et al, 2004). Acupuncture at such acupoints as Baihui (DU-20), Hegu (LI-4), Zhongji (CV-3), Guanyuan (CV-4) and Qihai (CV-6) has also shown satisfactory curative effects in treating primary dysmenorrhea (Habek et al, 2003).…”
Section: Dysmenorrheamentioning
confidence: 99%
“…A recent research showed that acupuncture point injection with vitamin K can alleviate acute menstrual pain, and the relief extended through the nontreatment follow-up cycles in an uncontrolled pilot study, which was conducted in two countries (Wang et al, 2004). Acupuncture at such acupoints as Baihui (DU-20), Hegu (LI-4), Zhongji (CV-3), Guanyuan (CV-4) and Qihai (CV-6) has also shown satisfactory curative effects in treating primary dysmenorrhea (Habek et al, 2003).…”
Section: Dysmenorrheamentioning
confidence: 99%
“…Two studies 35,36 were duplicated articles. The remaining 36 studies were further evaluated with regard to randomisation; five trials [37][38][39][40][41] did not mention randomisation and four trials [42][43][44][45] were found to be quasi-randomised trials. The remaining 27 studies, involving 2960 subjects, met our inclusion criteria and were systematically reviewed.…”
Section: Study Descriptionmentioning
confidence: 99%
“…In other studies on dysmenorrhea, pains have been relieved with various treatment approaches that include non-steroidal anti-inflammatory drugs (Namavar Jahromi et al, 2003;Mehlisch et al, 2003;Milsom et al, 2002), oral contraception (Milsom and Andersch, 1984;Davis and Westhoff, 2001;Callejo et al, 2003), acupuncture (Helms, 1987;Habek et al, 2003), transcutaneous electrical nerve stimulation (Dawood and Ramos, 1990;Kaplan et al, 1997), and microwave diathermy treatment (Vance et al, 1996). However, results of these treatments were subjective.…”
Section: Introductionmentioning
confidence: 99%